Enhancement of vehicle stability based on coordinated active rear steering and additional yaw moment. (31st August 2022) - Wang, Ping; Ding, Xiaodong; Lin, Jiamei; Zhao, Yongqiang; Li, Jun
To improve the handling and manoeuvrability of four-wheel steer (4WS) and in-wheel motor-driven electric vehicle (EV) under critical conditions, a coordinated control method combining active rear-wheel steering (ARS) and additional yaw moment control in the form of additional drive torque distribution is proposed. Considering the nonlinear properties of tyre force, a nonlinear model predictive controller (NMPC) is designed to track the desired yaw rate and constrain the sideslip angle. Meanwhile, the actuator and security constraints are satisfied effectively. Finally, the control performance is investigated by co-simulation with MATLAB/Simulink and CarSim. The results show that the vehicle longitudinal and lateral stability are both efficiently enhanced under extreme conditions.